Targeting c-MYC in Platinum-Resistant Ovarian Cancer - Reyes-González, Jeyshka M; Armaiz-Peña, Guillermo N; Mangala, Lingegowda S; Valiyeva, Fatma; Ivan, Cristina; Pradeep, Sunila; Echevarría-Vargas, Ileabett M; Rivera-Reyes, Adrian; Sood, Anil K; Vivas-Mejía, Pablo E (Molecular cancer therapeutics, 2015)
The purpose of this study was to investigate the molecular and therapeutic effects of siRNA-mediated c-MYC silencing in cisplatin-resistant ovarian cancer. Statistical analysis of patient's data extracted from The Cancer Genome Atlas (TCGA) portal showed that the disease-free (DFS) and the overall (OS) survival were decreased in ovarian cancer patients with high c-MYC mRNA levels. Furthermore, analysis of a panel of ovarian cancer cell lines showed that c-MYC protein levels were higher in cisplatin-resistant cells when compared with their cisplatin-sensitive counterparts. In vitro cell viability, growth, cell-cycle progression, and apoptosis, as well as in vivo therapeutic effectiveness in murine xenograft models, were also assessed following siRNA-mediated c-MYC silencing in cisplatin-resistant ovarian cancer cells. Significant inhibition of cell growth and viability, cell-cycle arrest, and activation of apoptosis were observed upon siRNA-mediated c-MYC depletion. In addition, single weekly doses of c-MYC-siRNA incorporated into 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000] (DSPE-PEG-2000)-based nanoliposomes resulted in significant reduction in tumor growth. These findings identify c-MYC as a potential therapeutic target for ovarian cancers expressing high levels of this oncoprotein.